Prison Sentences and Vocational Training in Cases of Sexual Assault Committed by Minors (A Study of Decision Number 56/Pid. Sus/2024/PN Tjk) - Prasetyawati, S Endang; Ramasari, Risti Dwi; Nababan, Kalfin Febrian (The Future of Education Journal, 2025)
Criminal acts committed by children, including forced sexual intercourse, are influenced by negative environments, lack of sex education, and dysfunctional family conditions. A rehabilitative approach, such as vocational training, is more effective than imprisonment in rebuilding a child's future. Prevention requires collaboration between the government, society, and families, focusing on sex education, a safe environment, and the elimination of stigma against victims. These efforts are essential to reduce similar cases and to protect children's rights in the future. How is the implementation of imprisonment and vocational training sanctions in the case of forced sexual intercourse committed by a child based on Decision Number 56/PID.Sus-Anak/2024/PN Tjk? And what are the judge’s considerations in applying the imprisonment and vocational training sanctions in the case of forced sexual intercourse committed by a child based on Decision Number 56/PID.Sus-Anak/2024/PN Tjk? The research method uses a normative juridical approach, which involves examining existing laws and regulations, and an empirical approach, which includes field observations through interviews to address issues related to the research problem.